2000
DOI: 10.1128/aac.44.2.294-303.2000
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Passage-Selected Vancomycin-Resistant Staphylococcus aureus Strains of Diverse Parental Backgrounds

Abstract: A series of 12 Staphylococcus aureus strains of various genetic backgrounds, methicillin resistance levels, and autolytic activities were subjected to selection for the glycopeptide-intermediate S. aureus (GISA) susceptibility phenotype on increasing concentrations of vancomycin. Six strains acquired the phenotype rapidly, two did so slowly, and four failed to do so. The vancomycin MICs for the GISA strains ranged from 4 to 16 g/ml, were stable to 20 nonselective passages, and expressed resistance homogeneousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
146
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 114 publications
(151 citation statements)
references
References 32 publications
4
146
1
Order By: Relevance
“…For instance, the intermediate vancomycin-resistance phenotype in S. aureus is due to an increased amount of non-amidated glutamine residues in the peptidoglycan. It has been suggested that the increased resistance in these strains is due to the "affinity trapping" of vancomycin in the thickened cell wall [17,18].…”
Section: Cell Permeabilitymentioning
confidence: 99%
“…For instance, the intermediate vancomycin-resistance phenotype in S. aureus is due to an increased amount of non-amidated glutamine residues in the peptidoglycan. It has been suggested that the increased resistance in these strains is due to the "affinity trapping" of vancomycin in the thickened cell wall [17,18].…”
Section: Cell Permeabilitymentioning
confidence: 99%
“…5 ìg ml À1 for BB270 V5 ) and not the actual vancomycin MIC (Pfeltz et al, 2000). The MICs of the strains for vancomycin, teicoplanin and oxacillin and other characteristics of these strains were described by Pfeltz et al (2000).…”
Section: Methodsmentioning
confidence: 99%
“…BB270), and the number associated with the subscript V (such as V5) refers to the vancomycin concentration at which the strain was maintained directly following VISA phenotype selection (e.g. 5 ìg ml À1 for BB270 V5 ) and not the actual vancomycin MIC (Pfeltz et al, 2000). The MICs of the strains for vancomycin, teicoplanin and oxacillin and other characteristics of these strains were described by Pfeltz et al (2000).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations